Peranan mahasiswa dalam mengatasi krisis identitas nasional - subhi, Irfan (Maliki Interdisciplinary Journal, 2025)
The relationship between students in overcoming the national identity crisis has a significant impact on the identity crisis that is rampant in today's era, this incident occurs due to the many cultures that enter society. Identity crisis is a phenomenon where someone questions their existence in this world, while the national identity crisis is a condition when national identity experiences instability, this causes some citizens to forget their original culture and tend to be more inclined towards foreign cultures.This study aims to find out about the role of students in overcoming the national identity crisis that is rampant in society today, Students will develop local culture to rebuild national identity in order to realize unity and togetherness. The writing of this journal uses a literature review system targeting students in Indonesia, regarding the national identity crisis, the data taken in this writing includes several sources.The results of this study show significant progress where students play a role in realizing national identity in several ways, one of which is holding events that preserve local culture such as holding dance competitions in elementary schools, because education about local culture must be given from an early age.